Soviet self-hatred : the secret identities of postsocialism in contemporary Russia - Borenstein, Eliot, 1966- (Cornell University Press, 2023)
"As Borenstein shows in his readings of a range of popular culture texts, the imaginary identities Russians have been trying on since the Soviet collapse reflect an aggressive, often outward-facing self-hatred that allows some Russians to come to terms with their country's standing in the world, the social and economic misery, and the dominance of oligarchism and Putinsim"-